The Impact of Arts Integration on the Learning and Social Abilities of Students with Disabilities: An Approach to an Inclusive Classroom - Shouma, Madiha (2020)
Arts Integration (AI) is known as an effective teaching method which contributes to students’ engagement and learning in the classroom. It is flexible and can be altered or modified to fit an individual student’s needs. This study aims to determine how AI can contribute to the academic and social development of students with disabilities in the classroom. Building on existing literature on Arts Integration in education, it asks: What is the impact of AI on the educational and social development of students with disabilities? How does Arts integration in the curriculum contribute to effective inclusion in the classroom? What are teachers’ attitudes in the Emirate of Sharjah towards promoting arts integration in their classrooms? How involved and/or aware are caregivers about Art Integration? Based on a review of the literature on Arts Integration and theories of its impact on students with disabilities, a case study was conducted in one of the schools in the United Arab Emirates, specifically in the Emirate of Sharjah. The case study examined the impact of AI on the academic and social development of 4 elementary students with different disabilities. Moreover, a printed survey was distributed to the teachers and the Special Educational Needs Coordinator (SENCO) from the same school to measure their awareness and attitudes towards AI in their classrooms. In addition, through a collaboration with an educational governmental institute in Sharjah that caters to the needs of young adults with disabilities, an online survey was sent to their database -which includes caregivers of students with disabilities across Sharjah- to measure their knowledge and level of involvement in AI. The results indicate that AI has indeed a positive impact on the academic and social development of students with disabilities. Moreover, the results of the teachers’ survey (TWAS) show an incredible level of teachers’ awareness and willingness to increase the integration of art in their classrooms. Last but not least, the caregivers survey also showed how parents strongly encourage AI as they can see its impact on their children’s abilities and their attitude in social environments inside the house and inside the school. On these bases, it is recommended that educators consider Arts Integration as a key factor in their classroom as it provides information to a wide range of learners, multiple means for all students to express their understanding, and better engagement for all students in participatory, collaborative and developmental learning experiences. Further research is needed to identify the effectiveness of AI on different ages and different disabilities. Hence, create a clear and unified framework for teachers to practice AI in the inclusive classroom.